Expressão de HSP27 e razão entre os índices de proliferação celular e apoptose em carcinoma de mama com e sem metástases axilares - Birnfeld, Clarice Martins Feyh (2014)
Objectives: To evaluate the expression of Hsp27 by immunohistochemistry in tissue samples of invasive ductal carcinoma in women with and without the presence of metastasis in sentinel axillary lymph node compared to samples from patients diagnosed with fibrocystic changes in breast tissue. In addition, to study the relationship between the rate of cell proliferation and apoptosis by evaluating the expression of Ki-67 protein and caspase-3 by immunohistochemistry. Material and Methods: A cross- sectional study was designed to select patients treated at Hospital São Lucas of PUCRS between September 2001 and October 2009. The patients were divided in three groups: 25 patients diagnosed with invasive ductal carcinoma of breast with axillary lymph node metastasis, 25 patients with invasive ductal carcinoma of breast without axillary lymph node metastasis and a control group composed by tissue samples of 25 patients diagnosed with fibrocystic change of the breast. The expression of Hsp27, Ki-67 and caspase 3 expression was evaluated by image analysis and the rate of proliferation (Ki-67) and apoptosis (caspase 3) was calculated for the three groups. Results: The present study showed an increased expression of Hsp27 in the group of invasive ductal carcinomas without metastasis as compared to the control group. There was no significant difference of expression of Hsp27 between the group of ductal carcinoma with axillary metastasis and the control group. The expression of Hsp27 was significantly higher in the group without axillary metastasis as compared to the group with metastasis in both the primary tumor (<0.001) and the respective lymph node tissue samples (=0.003). The expression of Ki-67 and the rate of proliferation (ki-67) and apoptosis (caspase 3) were significantly higher in the groups with invasive ductal carcinoma as compared to the control group. There was no difference in the expression of Ki-67 and the rate of proliferation and apoptosis between the two groups of invasive ductal carcinoma. There was no significant difference in the expression of caspase 3 among the three groups. Conclusion: The quantitative analysis of Hsp27 demonstrated increased expression of this protein in carcinomas without axillary metastases, with a significantly higher expression in the primary tumor and lymph node tissue samples of this group as compared to the group without axillary metastasis. Although the methodology employed and the number of cases evaluated in this work do not allow one to conclude that such behavior in metastatic ductal carcinomas of breast is constant, such finding warrants further investigation.